Systematic Review: Depression and Anxiety Prevalence in Bladder Cancer Patients - Vartolomei, Liliana (Bladder Cancer, 2018)
BACKGROUND: Depression affects more than 300 million people of all ages worldwide. In patients with cancer the reported prevalence is up to 24%. OBJECTIVE: To systematically review the literature to report the prevalence of depression and anxiety among patients with bladder cancer (BC). METHODS: Web of Science, MEDLINE/PubMed, and The Cochrane Library were searched between January and March 2018 using the terms “bladder carcinoma OR bladder cancer AND depression OR anxiety”. RESULTS: Thirteen studies encompassing 1659 patients with BC were included. Six studies assessed depression prior and after treatment at 1, 6 and 12 months. Three were conducted in the US, one each in Turkey, Sweden/Egypt and China. Four studies showed a reduction of depression after radical cystectomy (RC) at 1, 6 and 12 months, respectively. Contrary, two studies showed no significant difference in depression between baseline and follow-up. Four studies investigated anxiety; they reported a slight reduction in anxiety score compared to baseline. Seven additional studies reported the prevalence of depression and anxiety (five studies) among patients with BC at a specific time-point. Studies were conducted in Sweden (2), Italy, Greece, US, China and Spain. Pretreatment depression rates ranged from 5.7 to 23.1% and post-treatment from 4.7 to 78%. Post-treatment anxiety rates ranged from 12.5 to 71.3%. CONCLUSIONS: The prevalence of reported depression and anxiety among BC patients is high with large geographic heterogeneity. Gender and geriatric specific screening and management for anxiety and depression should be implemented to alleviate suffering.